الإصلاح الاقتصادي للقطاع العام الصناعي السوري في إطار التجربة الماليزية وصولا إلى اقتصاد السوق الاجتماعي - محمود, يوسف; شرف, سمير; عــلي, شــادي محــسن (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول البحث واقع وإشكالات القطاع العام الصناعي السوري, بهدف العمل على إيجاد أنسب الطرق لحلها مع الحفاظ على هذا القطاع من الانهيار, وإمكانية تفعيل دوره الاقتصادي الإيجابي في دعم الدخل القومي و تطوير المنتج الوطني ووضع الأسس الاقتصادية الضرورية بالاعتماد على التجربة الماليزية كي يعمل وفق آلية تنسجم مع الاقتصاد العالمي و يحقق بنفس الوقت الهدف الاجتماعي الذي بني من أجله هذا القطاع. وبتجرد عن المفهوم الإيديولوجي يشير البحث إلى الواقع و المتطلبات التي يمكن من خلالها تحقيق الإصلاح الاقتصادي وصولا إلى نموذج يمثل خصوصية الاقتصاد السوري والذي يعكس البعد الاجتماعي لأي خطوة من خطوات الإصلاح تطبيقا لمفهوم اقتصاد السوق الاجتماعي الذي يعنى بالدرجة الأولى بحماية الطبقات الشعبية من أي اضطراب ينعكس سلباً على المجتمع السوري. This paper aims at discussing the case of public industrial sector, and the possibility of dealing with its problems and obstacles. It also tries to find the most appropriate ways to solve such problems, while maintaining the sector, and reinforcing its positive economic role in supporting national income, developing national product based on the Malaysian experience. The paper goes a step further towards giving an overall view of what seems workable in achieving economic reform which, in turn, would be of great relevance to the full achievement of a model representing the privacy of Syrian economy and reflecting the social dimension of any reform step in relation to the concept of a social market economy, which is primarily concerned with protecting the working classes from any disturbance that may reflect negatively on the Syrian society.